DETERMINAÇÃO DO ESTADO DE SAÚDE DA BATERIA CHUMBO-ÁCIDO - Luczkievicz, Fabiana Regina Grigolo (2011)
In this work, a new method for the determination of capacity and state of health of lead-acid batteries is proposed. The proposed method uses only one characteristic point of the discharge curve at the end of the "coup de fouet" by applying Peukert`s equation. While the traditional method using full discharges requires experiments of up to 20 hours for measurement of the battery capacity, the proposed method allows the estimation of the same parameter in only 3% of total time. The method also allows estimating the parameters of the Peukert equation, important for the morphological characterization of the battery active material. The method under study was tested for plans, pasted and tubular electrodes, by applying galvanostatic charge/discharge cycles at different currents. Moreover, the work allows clarify several points about the mechanism of formation of the "coup de fouet" about which little is known.